2020
DOI: 10.3390/cancers12123497
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Response-Adapted Treatment in Multiple Myeloma

Abstract: Myeloma therapeutic strategies have been adapted to patients’ age and comorbidities for a long time. However, although cytogenetics and clinical presentations (plasmablastic cytology; extramedullary disease) are major prognostic factors, until recently, all patients received the same treatment whatever their initial risk. No strong evidence allows us to use a personalized treatment according to one cytogenetic abnormality in newly diagnosed myeloma. Retrospective studies showed a benefit of a double autologous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 101 publications
0
9
0
Order By: Relevance
“…The International Staging System, which is based on serum beta-2 microglobulin and albumin levels, is the most widely adopted in multiple myeloma and is also correlated with the prognosis of the disease [40]. Assessment of bone marrow involvement by malignant plasma cells is an important element in the diagnosis and follow-up of patients with multiple myeloma and other plasma cell dyscrasias [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The International Staging System, which is based on serum beta-2 microglobulin and albumin levels, is the most widely adopted in multiple myeloma and is also correlated with the prognosis of the disease [40]. Assessment of bone marrow involvement by malignant plasma cells is an important element in the diagnosis and follow-up of patients with multiple myeloma and other plasma cell dyscrasias [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…After initial induction, high‐dose therapy and ASCT followed by IMiDs and/or PIs maintenance, prolongs PFS and OS in high‐risk NDMM; however, most patients eventually relapse and suffer early death 23 . In this single‐center, single‐arm, exploratory clinical trial, which to the best of our knowledge is the first of its kind, we found that posttransplant infusion of autologous dual‐antigen–targeting (anti‐CD19 and anti‐BCMA) CAR T cells followed by lenalidomide maintenance shows promising efficacy and favorable safety.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the significant advancements in therapeutics for MM patients, MM remains an incurable disease characterized by multiple remissions and relapses. The current clinical practice focuses on identifying high-risk patients and increasing the quality of life [ 117 , 118 ]. High-risk patients are determined based on many features, including frailty status, aggressiveness in clinical presentation, cytogenic abnormalities, mutations, biochemical abnormalities, prognostic scores, and the ISS risk model [ 119 ].…”
Section: Multiple Myeloma (Mm) Treatmentmentioning
confidence: 99%